Psychosocial Stress and Psychosis. A Review of the Neurobiological Mechanisms and the Evidence for Gene-Stress Interaction - van Winkel, Ruud (Oxford University Press, 2008)
This article presents evidence suggesting that psychosocial stress may increase risk for psychosis, especially in the case of cumulative exposure. A heuristically useful framework to study the underlying mechanisms is the concept of “behavioral sensitization” that stipulates that exposure to psychosocial stress—such as life events, childhood trauma, or discriminatory experiences—may progressively increase the behavioral and biological response to subsequent exposures. The neurobiological substrate of sensitization may involve dysregulation of the hypothalamus-pituitary-adrenal axis, contributing to a hypothesized final common pathway of dopamine sensitization in mesolimbic areas and increased stress-induced striatal dopamine release. It is argued that, in order to reconcile genetic and environmental influences on the development of psychosis, gene-environment interactions may be an important mechanism in explaining between-subject differences in risk following (cumulative) exposure to psychosocial stress. To date, most studies suggestive of gene-stress interaction have used proxy measures for genetic vulnerability such as a family history of psychosis; studies investigating interactions between molecular genetic measures and psychosocial stressors are still relatively scarce. Preliminary evidence suggests that polymorphisms within the catechol-O-methyltransferase and brain-derived neurotrophic factor genes may interact with psychosocial stress in the development of psychosis; however, extensive further investigations are required to confirm this.